Development of a measurement system for noise and vibration of combine harvester - Yilmaz, Deniz; Gökduman, Mehmet Emin (International Journal of Agricultural and Biological Engineering, 2020)
Combine harvesters are important in that grain and legumes directly affect the production economy. On the other hand, it forms an important branch of the agricultural machinery sector. There are many unknown constraints on machines when harvesting with a combine harvester, including the noise and vibration that occur in the combine harvester thresher. This study aims to analyze noise and vibration in conventional combine harvesters using sensors. Two accelerometers were installed on each side of the concave and two microphones were used to register the noise of the threshing process. The result showed that effects of machine speeds (3.5 km/h, 4.5 km/h and 5.5 km/h) and rotor speeds (950 r/min, 850 r/min and 950 r/min) were significantly important for the mean range values of the left and right accelerometer in the X, Y and Z direction. The machine’s speed and rotor speed were not significantly important for the mean range values of the left and right microphones. Keywords: measurement, combine harvester, sensors, noise, vibration DOI: 10.25165/j.ijabe.20201306.5554 Citation: Yılmaz D, Gökduman M E. Development of a measurement system for noise and vibration of combine harvester. Int J Agric & Biol Eng, 2020; 13(6): 104–108.